Building sustainable ecosystems through community education - Richard Hennery; Ochen Mayaini; Isabelle Voorspuy (Pachyderm)
Borana Conservancy lies in the Ewaso Nyiro ecosystem in Laikipia County, just north of the Equator in Kenya. Borana, together with its neighbour Lewa Wildlife Conservancy (LWC), is now home to 132 eastern black rhinos (Diceros bicornis michaeli) and 122 southern white rhinos (Ceratotherium simum simum). The population of black rhinos represents at least 13% of Kenya’s black rhino population. Borana’s work revolves around ‘the four Cs’: conservation, community, culture and commerce, showcasing best practices for sustainable living. The long-term goal of the Conservancy is to provide a sustainable ecosystem, in partnership with its neighbours and community, for critically endangered species on the brink of extinction.